PERINATAL RISK AND PREVENTION OF PRETERM BIRTH - Yunusova Aziza Rakhmatilloyevna (Journal of Science in Medicine and Life, 2024)
Primary weakness of birth was detected 3 times more often in the average risk group, which is due to the use of a non-pathogenic method of preparation of the birth canal (kelp) and the frequent use of uterotonic drugs to induce labor. may be associated with rapid use. . Secondary vulnerability is specific to women who are at high risk due to the preponderance of multiparous women. Particular attention is paid to such birth complications as placental attachment and its defect, which are characteristic of women at high risk. Undoubtedly, this is related to the disruption of chorion formation as a result of the effects of conception factors (extragenital diseases, in particular, anemia, inflammatory diseases of the genitals) in the early stages of pregnancy.